2015
DOI: 10.1093/abbs/gmv081
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of Cu<sup>2+</sup>-binding on oligomerization of human and rabbit prion proteins

Abstract: The cellular prion protein (PrP(C)) is a kind of cell-surface Cu(2+)-binding glycoprotein. The oligomerization of PrP(C) is highly related to transmissible spongiform encephalopathies (TSEs). Cu(2+) plays a vital role in the oligomerization of PrP(C), and participates in the pathogenic process of TSE diseases. It is expected that Cu(2+)-binding has different effects on the oligomerization of TSE-sensitive human PrP(C) (HuPrP(C)) and TSE-resistant rabbit PrP(C) (RaPrP(C)). However, the details of the distinct e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Heme proteins are a large class of metalloenzymes crucial for biological systems, which bind the heme group non-covalently such as heme b (Fe-protoporphyrin IX) or covalently such as heme c via thioether bonds and other heme-protein cross-links [127]. The heme b group can be removed from the protein scaffold under acidic conditions, producing the corresponding apo-proteins [128].…”
Section: Metallo-porphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heme proteins are a large class of metalloenzymes crucial for biological systems, which bind the heme group non-covalently such as heme b (Fe-protoporphyrin IX) or covalently such as heme c via thioether bonds and other heme-protein cross-links [127]. The heme b group can be removed from the protein scaffold under acidic conditions, producing the corresponding apo-proteins [128].…”
Section: Metallo-porphyrinsmentioning
confidence: 99%
“…The chemical property of heme are strongly affected by its substitutions, especially those at the 2-and 4-positions, as in most post-translational modifications [127]. The modified heme analogs can then be used to fine-tune the property and function of heme enzymes.…”
Section: Heme Analogsmentioning
confidence: 99%
“…The effect of Cu(II)-binding was also assessed on the oligomerization of PrP C . Lin et al showed that Cu(II)-binding promoted oligomerization of a susceptible species more significantly than that of a resistant species, suggesting that the low susceptibility to Cu(II) in the resistant species might results in a weak risk of Cu(II)-induced TSE diseases [141]. In support to the role of the non-OR region for prion conversion, transgenic mice, TgPrP(H95G), with an amino acid replacement at residue H95 showed shorter disease progression than WT control mice and classical clinical signs of TSE [142].…”
Section: Structural Consequences Of Copper Bindingmentioning
confidence: 99%